2010
DOI: 10.3324/haematol.2010.029660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gene expression signatures predictive of cytogenetic and molecular subtypes of pediatric acute myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPediatric acute myeloid leukemia is a heterogeneous disease characterized by non-random genetic aberrations related to outcome. The genetic subtype is currently detected by different diagnostic procedures which differ in success rate and/or specificity. Design and MethodsWe examined the potential of gene expression profiles to classify pediatric acute myeloid leukemia. Gene expression microarray data of 237 children with acute myeloid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 65 publications
3
116
0
1
Order By: Relevance
“…However, GEP has illustrated that current diagnostic techniques do not guarantee 100% sensitivity for detection of MLL rearrangements. 12 For three cases that clustered together with those with an MLL rearrangement, long-distance inverse-PCR showed that an MLL rearrangement was present, which had not been detected by split-signal FISH. This also shows the advantage of long-distance inverse-PCR, which can detect all translocation partners of MLL using only a little amount of DNA, Table 2 Outcome of MLL-rearranged AML per study group compared with outcome in the total group of pediatric AML Abbreviations: AML, acute myeloid leukemia; EFS, event-free survival; MLL, mixed-lineage leukemia; OS, overall survival; 5y-pEFS, probability of EFS at 5 years from diagnosis; 5y-pOS, probability of OS at 5 years from diagnosis; y, years.…”
Section: The Detection Of Mll Rearrangementsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, GEP has illustrated that current diagnostic techniques do not guarantee 100% sensitivity for detection of MLL rearrangements. 12 For three cases that clustered together with those with an MLL rearrangement, long-distance inverse-PCR showed that an MLL rearrangement was present, which had not been detected by split-signal FISH. This also shows the advantage of long-distance inverse-PCR, which can detect all translocation partners of MLL using only a little amount of DNA, Table 2 Outcome of MLL-rearranged AML per study group compared with outcome in the total group of pediatric AML Abbreviations: AML, acute myeloid leukemia; EFS, event-free survival; MLL, mixed-lineage leukemia; OS, overall survival; 5y-pEFS, probability of EFS at 5 years from diagnosis; 5y-pOS, probability of OS at 5 years from diagnosis; y, years.…”
Section: The Detection Of Mll Rearrangementsmentioning
confidence: 93%
“…11 In pediatric AML, MLL-rearranged AML presents with a distinct, unique, expression profile as compared with MLL-PTD. 12,13 Therefore, MLL-rearranged AML and MLL-PTD are considered two different entities.…”
Section: Introductionmentioning
confidence: 99%
“…(Ross, et al 2004) This was confirmed by Balgobind et al in an independent study of 237 children with pediatric AML (specificity and sensitivity for discovery of the indicated cytogenetic subclasses was 92% and 99%, respectively). (Balgobind, et al 2011b) However, in the latter study no general predictive gene expression signatures were found for the molecular genetic aberrations NPM1, CEBPA,or KIT. This may have been caused either by a low frequency of certain mutations, but also by underlying cytogenetics or cell line of origin.…”
Section: Gene Expression Profiling As a Diagnostic Toolmentioning
confidence: 94%
“…In an exclusively paediatric cohort (n=130) gene expression profiling study distinct clusters were identified including t(15;17), t(8;21), inv(16), MLL chimeric genes and FAB M7 that could be used with 93% accuracy to predict clusters in both a validated paediatric and adult cohort [76]. Improved predictions with 99% accuracy could be made from gene expression signatures from one paediatric cohort (n=237) on exclusively paediatric validation sets [77]. This higher accuracy may reflect age related differences to be discovered when 11 comparing adult and paediatric datasets.…”
Section: Age and Gene Expression In Amlmentioning
confidence: 99%